2016
DOI: 10.18805/ijar.8599
|View full text |Cite
|
Sign up to set email alerts
|

Cross-regional analysis on usage of Indigenous Technical Knowledge in dairy farming

Abstract: Farmers in India have been using traditional health care practices in dairy farming since time immemorial. Present paper is an attempt to review the Indigenous Technical Knowledge (ITK) practised and documented across five regions in India viz., North, South, East, West and North East regions to understand the prevalence of ITKs and its dynamics of usage across the country. Cross regional analysis of location specificity of different ITKs, similarities and variation in ingredients usage and researchable issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…ii Sarita et al (2017) and reported that only 42.8 per cent of respondents knew only two harms adverse effects followed by < 2 harms (36.4%) and > 2 harms of ectoparasites (20.8%). There is need of extension programmes to educate the farmers about diseases transmitted through ectoparasites and to reduce the economic loss to the farmers (Ponnusamy et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ii Sarita et al (2017) and reported that only 42.8 per cent of respondents knew only two harms adverse effects followed by < 2 harms (36.4%) and > 2 harms of ectoparasites (20.8%). There is need of extension programmes to educate the farmers about diseases transmitted through ectoparasites and to reduce the economic loss to the farmers (Ponnusamy et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that more than fifty per cent dairy farmers had partially adopted the practice of maintaining the proper distance between the animals to avoid the transfer of ectoparasites from one animal to another (59.33%). Majority of dairy farmers (93.33%) had not adopted insects preventive net followed by calcium carbonate (83.67%) and home remedies like neem oils (62.67%) to prevent & control of bovine ectoparasites (Ponnusamy et al 2017). More than half (54.33%) of dairy farmers had fully adopted the practice of regular bathing of animals for effective control of ectoparasite.…”
Section: Resultsmentioning
confidence: 99%
“…Rationality refers to the degree to which ITKs can be explained or supported with scientific explanations, or established based on long term experiences (Husain and Sundaramari, 2011;Ponnusamy et al, 2017). Rationality scale (Hiranand, 1979) with some modification was used to judge the rationality of the ITK.…”
Section: Assessment Of Rationality and Effectiveness Of Itksmentioning
confidence: 99%
“…Concerted efforts need to be oriented toward technology demonstration and social engagement among women for enhancing farming standards [ 9 ]. Practices derived from indigenous system have the main role in farming engaged by resource-poor farmers [ 10 ]. These knowledge systems can complement formal system in controlling livestock ailments [ 11 ] and provide solutions where accessibility is constraint [ 12 ].…”
Section: Introductionmentioning
confidence: 99%